Entre herejía y hechicería: Isabel María de Montoya ante la Inquisición de Toledo (1671) - Vincent Parello (Les Cahiers de Framespa)
The trial of Isabel María de Montoya instructed by the Toledo inquisitorial court in 1671, allows us to enter the realms of superstition and popular beliefs in which the sacred and the secular mingle and saints alternate with daemons. Even if the Fathers of the Church have tried to set up a frontier between the law of Christ and the law of Satan, both realms intertwine within the mentality of the modern man.